Pseudo-Orbital Apex Syndrome in the Acute Trauma Setting Due to Ipsilateral Dissection of Internal Carotid Artery. Issue 4 (July 2016) - Anders, Ursula M; Taylor, Elise J.; Martel, Joseph R.; Martel, James B.
Abstract : Traumatic causes of orbital apex and superior orbital fissure syndrome are uncommon. The authors present the first case of a traumatic superior orbital fissure syndrome simulating orbital apex syndrome, with loss of vision from posterior ischemic optic neuropathy. A 35-year-old man was initially felt to have a right orbital apex syndrome with left craniofacial and orbital trauma. CT revealed left orbital fractures, a right superior orbital fissure fracture, a retained metallic foreign body in the right sphenoid sinus, and a right frontoparietal subdural hematoma. CT angiography showed a secondary dissection and occlusion of the right internal carotid artery from osseous erosion of the posterolateral wall of the sphenoid sinus. Internal carotid artery dissection is a possible, though rare, cause of ischemic optic neuropathy. The right pseudo-orbital apex syndrome resulted from a mechanical superior orbital fissure syndrome and posterior ischemic optic neuropathy from an internal carotid artery dissection. Abstract : A patient presented with a pseudo-orbital apex syndrome and contralateral orbital trauma, but was diagnosed with a superior orbital fissure syndrome with secondary posterior ischemic optic neuropathy from a dissecting carotid artery after diagnostic imaging.